Supervisi Kepala Sekolah dalam Meningkatkan Kompetensi Guru di SMP IT Prima Mandiri Percut Sei Tuan - Akhirul Sa’Ban; Sri Nurabdiah Pratiwi; Salim Aktar (UMSU, 2023)
The aim of this study uses qualitative approach where by the researcher conducted the research directly in the field. The technique of data collecting was by observing, interviewing and doing documentation study at SMP IT Prima Mandiri. The informan in the this research are the principal,the vice principal and the discipline teacher. The interactive analisys model of miles and Huberman was used to analyse the data, data reduction, data presentation and conclusion. The tringulation technique, transferability test,dependability,and confirmability were used to verify the validity of the data. The problem of this researeh is to show that the learuing process is not as maximal as hoped in pedagogic competency,professional competency, sosial competency,and attitude competency in improving the teacher‟s competency at SMP IT Prima Mandiri.The findings of this study revealed three things, (1) the supervision program planning which was conducted by the principal in increasing the teacher‟s competence that had been arranged correctly based on the existing provisions,(2) the supervision technique which was conducted by the principal in increasing the teacher‟s competence was by using supervision technique individually and group,(3) the evalution of the supervision done by the principal in increasing the teacher‟s competence was marked by the teacher‟s performance. By Conducting this supervision program, it helped the teachers in facing every problem concerned with the learning process.